Increased postictal creatine kinase in epilepsy patients - L. V. Lipatova; I. V. Sakovsky (Эпилепсия и пароксизмальные состояния)
Excessive muscle activity during generalized convulsive seizures in epilepsy patients in some cases can cause significant changes in blood plasma biochemical parameters, increased level of a set of metabolites, particularly, serum creatine kinase, accompanied by azotemia, which leads to prominent diagnostic and therapeutic difficulties. It is necessary to monitor the creatine kinase concentration after seizures, especially in case of electrolyte disturbances. To correct elevated creatine kinase or myoglobin levels, infusion therapy, urine alkalinization along with diuretics administration should be performed.